Utilization of Next Generation Sequencing and Metabolomics in Human Microbiome Studies: Optimized Laboratory Methods and Exploratory Findings on Gut Microbiome and Metabolome Development in Early Life - Isokääntä, Heidi (fi=Turun yliopisto|en=University of Turku|, 2025)
The proportion of the gut microbiota dominates the total human microbiota, and its diversity and dynamic properties pose certain methodological challenges. With the development of methods, significant strides have been made in the field, such as population-level sample collections and high-performance analysis methods. On the other hand, although many health responses have been found, there is little information about the development of the microbiota and its metabolites. Timely developmental stages lay the foundation for a balanced gut microbiota that produces vital metabolic products to ensure growth and development. Early childhood microbial exposures prepare the individual’s tolerance to various exposures, and the immune defence is programmed to function according to prevailing conditions. In early childhood, breast milk plays a significant role in the development of the microbiota. In this dissertation, optimized protocols for DNA isolation in a microplate format and sample collection for faecal microbiota and metabolome studies were developed, and developmental patterns in early childhood gut microbiota and metabolome were mapped together with breast milk metabolites. The optimized sample collection and DNA isolation achieved seamless sample pre-processing, sufficient reproducibility, breakdown of hard-to-lyse cell membranes, and minimization of contamination. The connections between breastfeeding, human milk composition and the child’s gut microbiota and metabolome confirmed previously reported findings.

Suolistomikrobiston osuus dominoi ihmisen kokonaismikrobimäärää ja sen monimuotoisuus ja dynaamiset ominaisuudet asettavat tiettyjä menetelmällisiä haasteita. Menetelmäkehityksen myötä alalla on otettu merkittäviä harppauksia kuten väestötason näytekeräykset ja korkean suorituskyvyn analysointimenetelmät. Toisaalta vaikka löydettyjä terveysvasteita on paljon, mikrobiston ja sen metaboliittien kehityksestä on vain vähän tietoa. Oikea-aikaiset kehitysvaiheet luovat pohjan tasapainoiselle suolistomikrobistolle, joka tuottaa elintärkeitä aineenvaihdunnan tuotteita kasvun ja kehityksen takaamiseksi. Varhaislapsuuden mikrobialtistukset valmistelevat yksilön toleranssia erilaisille altisteille ja immuunipuolustus ohjelmoituu toimimaan vallitsevien olosuhteiden mukaan. Varhaislapsuudessa äidinmaito on merkittävässä roolissa mikrobiston kehittymisessä. Tässä väitöskirjassa kehitettiin optimoidut protokollat DNA-eristykseen kuoppalevyformaatissa ja näytteenkeräykseen ulosteen mikrobisto- ja metabolomitutkimukseen sekä kartoitettiin varhaislapsuuden kehityksellisiä reittejä suolistomikrobistossa ja -metabolomissa yhdessä äidinmaidon metaboliittien kanssa. Optimoidulla näytesäilytyksellä ja DNA-eristyksellä saavutettiin sujuva näytteenesikäsittely, riittävä toistettavuus, sitkeidenkin solukalvojen hajotus ja kontaminaatioiden minimointi. Imetyksen yhteydet lapsen suolistomikrobiston kehittymiseen vahvistivat jo aiemmin raportoituja löydöksiä.